Studentsâ€™ Perception of the Use of TalkEnglish.com in Teaching Speaking for ESP Class - Ria, Tiara Nove; Lestari, Sri; Mutiaraningrum, Ira; Arriyani, Nurfisi (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
The field of education has greatly benefited from the advancements in technology, resulting in more efficacious, interactive, comprehensive, and non-classroom-bound learning experiences. One such application is web-based learning, which employs the Internet as a means to facilitate the educational process. This modality of instruction addresses various challenges that are inherent in traditional pedagogical approaches, such as the limited time allocated for lecturers and students in classroom settings.Â  Despite an abundance of literature that has investigated the incorporation of technology in the teaching of spoken English, there is a scarcity of studies that specifically examine the utilization of the website, TalkEnglish.com.Specifically, in the context of teaching English for Business, which necessitates students to develop proficient and precise oral proficiency in the language, the present study aims to investigate the students' perception of the efficacy of TalkEnglish.com in honing their speaking skills. This study employed a descriptive qualitative design, where ten students from the Economic Faculty at Universitas Pandanaran were selected as participants. These participants utilized the website TalkEnglish.com to improve their speaking skills. Data was collected through a semi-interview approach and documentation method. The findings of the study indicate that the majority of the participants held a positive perception of TalkEnglish.com.